Implications for paediatric training and workforce from pandemic disruptions: A view from a tertiary hospital. (24th August 2022) - Gard, Jye; Cisternino, Angela; Polley, Clare; Gray, Amy
Abstract : Aim: To understand the lived experience of paediatric trainees in relation to their educational opportunities, workforce roles and the interplay between them, during pandemic disruptions. Methods: Twenty paediatric trainees working at Australian paediatric hospitals during the time of COVID‐19 restrictions were interviewed between July and November 2020. Based on a phenomenological approach, the interviews examined junior doctors' experiences in relation to medical education, adaptive education modes, learning opportunities and their workforce roles during the pandemic. Qualitative inductive thematic data analysis was used to develop a cohort narrative. Results: Four overarching themes were identified regarding trainee perceptions of the impact of COVID‐19 restrictions on learning opportunities, both positive and negative. These were: impaired rapport building, altered team role, altered care and education affordances versus access. Participants felt ill‐equipped to provide optimal clinical care during virtual and stifled in‐person consultations, detached from the multidisciplinary team, that changed work roles diminished their professional self‐worth, and that online learnings were advantageous if rostering afforded opportunities to engage with them. Conclusion: To equip paediatric trainees for the next steps in their careers, we suggest the following areas of focus: the use of new tools of rapport, smart investment in clinical moments, reconnection of multidisciplinary teams and learning, the support of online learning infrastructure with protected education time and roadmaps for learning, and teaching on how to triage information sources and alongside clinical visit types.